Turbulence : introduction to theory and applications of turbulent flows /: introduction to theory and applications of turbulent flows. (2016) - Westerweel, J; Boersma, Bendiks Jan, 1969-; Nieuwstadt, F. T. M (Frans T. M.), 1946-
No abstract available